Mycosporine-Like Amino Acids From Red Algae To Develop Natural Uv Sunscreens - Navarro Martinez, Nelso Patricio; Figueroa, F.L.; Korbee, N.; Bonomi, J.; Gómez, F.A.; de la Coba, F. (My University, 2018)
Mycosporine-like amino acids (MAAs) are molecules with low molecular weight, water-soluble, nitrogen enriched and absorption maxima in the UV region (310–365 nm). They are ideal sunscreens due to the high photo- and thermostability, strong UV absorption, energy dissipation as heat and short-lived excited state to avoid photochemical reactions (no photoproduct formation). These compounds are present mainly in autotrophic organisms, including red algae. The most common MAAs in these organisms are shinorine, palythine, palythinol, asterina-330, and porphyra-334, all of which have absorption maxima in the UV-A region (315-400 nm), whereas mycosporine-glycine has its absorption maximum in the UV-B region (310 nm). Due to their UV- absorption, antioxidant capacity among other physico-chemical features give MAAs a potential application in the prevention and therapeutic treatment of afflictions related to free-radical production and UV irradiation in humans. Sunscreens are available on the market, which are manufactured using porphyra-334 and shinorine, but these compounds have been isolated from one unique species. Thus, species with high MAA concentrations are desirable because of their enormous biotechnological application. In this chapter, we present a screening of both amount and composition of MAAs from different red algae species found in Europe, South America and Polar regions in different periods of the year, and different culture conditions in order to gather species with high MAA concentration or at least species that can change individual MAA concentration. The concentration of each MAA dependeds on the species but can also be adjusted in relation to changes in the quality and quantity of environmental radiation (e.g., UV-A, UV-B, and by PAR), as well as in relation to other environmental variables such as inorganic nitrogen availability, salinity, temperature, pH and phosphate. The influence of N on the accumulation of MAAs, both under artificial and solar UVR, in several macroalgae is presented. The MAA concentration can be increased (2-3 times) by the culture of red algae species in N enriched waters i.e., fishpond effluents in the frame of integrated multitrophic aquaculture, and species from upwelling areas also presented increasing contents of MAAs. UV screen photopotectors in the market including MAAs as potential use in natural cosmetics are reviewed.
Keywords: Antioxidant; Cosmetics; Maa Concentration; Red Algae; Sunscreens